2006
DOI: 10.1016/j.jcf.2005.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Calpain 10 and development of diabetes mellitus in cystic fibrosis

Abstract: Diabetes mellitus (DM) and abnormal glucose tolerance (IGT) are common in cystic fibrosis (CF). The loss of pancreatic beta-cells due to pancreatic fibrosis is thought to be one of the principal causes of diabetes in CF, but the aetiology of DM remains somewhat puzzling. Genetic factors may contribute to the development of CF related diabetes (CFRD). The purpose of this study was to investigate the role of polymorphisms in six genes on IGT or DM incidence. PCR and dHPLC were used to screen DNA samples for poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…Among Chinese, variation in SNP43 is positively associated with IR (OR=1.41, 95%CI=1.13-1.76) (Jing et al, 2012). Epidemiological studies in Japan (Shima et al, 2003) and France (Derbel et al, 2006) similarly concluded that SNP19 is involved in the pathogenesis of IR. CAPN10 is also related to several types of cancer (pancreatic, laryngeal, and gastric), and it belongs to the calpain family which contains several oncogenes and tumor suppressor genes (Liu et al, 2004;Fong et al, 2010;Moreno-Luna et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Among Chinese, variation in SNP43 is positively associated with IR (OR=1.41, 95%CI=1.13-1.76) (Jing et al, 2012). Epidemiological studies in Japan (Shima et al, 2003) and France (Derbel et al, 2006) similarly concluded that SNP19 is involved in the pathogenesis of IR. CAPN10 is also related to several types of cancer (pancreatic, laryngeal, and gastric), and it belongs to the calpain family which contains several oncogenes and tumor suppressor genes (Liu et al, 2004;Fong et al, 2010;Moreno-Luna et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Periferal insülin duyarlılıklarının normal olması ve geride kalan pankreasın β hücrelerinin normal sekretuvar fonksiyonlarını koruması nedeni ile; önemli derecede β hücre kütlesi azalmış olan KF'li hastalarında sadece hafif glukoz tolerans bozuklukları olduğu izlenebilmektedir (6). Toplumda T2DM gelişmesine yol açan bazı genetik varyasyonların ve gen polimorfizmlerin KFİDM gelişmesinde de rol oynayabileceği ve hastalığın daha erken yaşlarda görülmesine yol açabileceği belirtilmiştir (15,16). KFİDM gelişmesinde inkretin hormonlarının rolünün ne olduğu konusunda ise daha fazla çalışmaya ihtiyaç vardır (17,18).…”
Section: Discussionunclassified
“…Potential therapies for class-specific correction/modulation of underlying CFTR defects are indicated. *HGF, hepatocyte growth factor enhances CFTR retention/anchoring at the cell surface (another epithelial chloride/bicarbonate channel that interacts with CFTR), and single-nucleotide polymorphisms (SNPs) for type 2 diabetes at or near CDKAL1, CDKN2A/B, and IGF2BP2 were found to be associated with CFRD, as well (13), and Derbel et al (14) presented the first evidence for an involvement of a polymorphism in the CAPN10 gene in the pathogenesis of CFRD. A further candidate gene approach revealed the modifying effects of a variant in the TCF7L2 gene that associates with both type 2 diabetes and CFRD, supporting the concept that diabetes develops in patients who may have underlying susceptibility to b-cell dysfunction (15).…”
Section: Cftr Gene Mutations: Genotype-phenotype Correlationsmentioning
confidence: 99%